Prospecção na mobilidade aérea urbana: análise estrutural e de atores - Lima, Gabriel Caliente (Universidade Federal de São Carlos, 2026)
This research analyzes Urban Air Mobility (UAM) as a sociotechnical system in the process of innovation, aiming to understand the variables that structure its dynamics and the actors that condition its evolution. A qualitative, exploratory approach is adopted, combining a systematic literature review and prospective analysis. The systematic review made it possible to map the state of the art on the subject, identifying 255 studies and highlighting the multidimensional nature of UAM, with a concentration of publications in the fields of engineering, market studies, regulation, and information technology. The findings of the review indicate that the consolidation of UAM depends on coordinated progress across different dimensions, especially technological development, infrastructure, regulation, financing, and social acceptance. Based on this foundation, the prospective analysis showed that technological and regulatory variables play a central role in structuring the system, decisively conditioning the behavior of the other dimensions. Infrastructure, flight patterns, and autonomy stand out as linkage elements, as they connect structural decisions to the operational materialization of the concept. By contrast, public acceptance, privacy, noise, and environmental issues showed lower driving capacity, assuming a more reactive role and tending to become more relevant only after technological, regulatory, and operational conditions have advanced. With regard to the actors, an asymmetry of power was observed, with the predominance of the regulatory and financial domains, whose agents occupy the most influential positions in shaping the sector. eVTOL manufacturers and infrastructure actors proved to be strategic for the implementation of UAM, although they remain strongly conditioned by regulatory decisions and the availability of financing, while platforms and the public showed greater dependence and predominantly indirect influence. It is concluded that the evolution of UAM stems less from structural conflicts among actors and more from the need for coordination among technological, institutional, economic, and operational capacities. The results reinforce that UAM should not be understood merely as an aeronautical innovation, but rather as a systemic and multidimensional phenomenon whose feasibility depends on convergence among different areas and actors. As a contribution, this study offers an integrated interpretation of the theme, articulating recent scientific production with a prospective analysis of the conditions that may favor or constrain the consolidation of the concept.
Prospection in urban air mobility: structural and actor analysis
Keywords: Mobilidade Aérea Urbana; Prospecção; Revisão Sistemática de Literatura; Aviação; Urban Air Mobility; Prospective; Systematic Literature Review; Aviation; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DA PRODUCAO; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::PLANEJAMENTO EM CIENCIA E TECNOLOGIA; 9. Indústria, Inovação e Infraestrutura